Development of interactive e-LKPD based on creative thinking skills on the concept of environmental change - Ricky Ardiansah; Z. Zulfiani (University of Muhammadiyah Malang, 2023)
Students' worksheets (Lembar Kerja Peserta Didik/LKPD) are needed as alternative teaching materials in learning. This study aims to produce electronic students' worksheets (e-LKPD) based on creative thinking skills on the concept of environmental change. In addition, this study also aims to determine the level of validity, readability, and practicality of the Interactive e-LKPD developed. The research method used is Developmental Research using the stages of Akker et al which consists of 3 stages, namely: Analysis, Design and Development, and Evaluation Phase. Validity test results obtained an average percentage value of 90.06% with a very valid category. The readability test results obtained an average percentage value of 94.91% with a very positive category. The results of the practical test by biology teachers and students obtained an average percentage of 100% and 81.22%, with both categories being very practical. Based on the test results that have been done, it can be concluded that the Interactive E-LKPD is very feasible to use in learning activities. Therefore, the existence of interactive E-LKPD as a source of alternative teaching materials to develop students creative thinking skills in biology learning is in line with the implementation of Kurikulum Merdeka (Freedom Curriculum).